HEAT EXCHANGER NETWORK SYNTHESIS AND OPTIMIZATION BY PINCH ANALYSIS AND DIFFERENTIAL EVOLUTION METHOD - NGO , THI PHUONG THUY (2016)
Synthesis of Heat Exchanger Network (HEN) and optimization is a comprehensive method to design the network of heat exchangers for efficient heat recovery by cost-effective manner. It improves and optimizes the recycling energy and the heat exchange between hot and cold streams to reduce the heating and cooling utility. Most of the techniques for optimization HENused mathematical programming which needs a good initial assumption, solving time and computer resources. The current research is focused on designing optimum heat exchanger system with minimum total cost in sequential. This metadology way uses an algorithm which combines Pinch Design Method and Differential Evolution Method. In this technique, the Heat Exchanger Network synthesis is carried out in three levels. First, the minimum temperature difference is optimized by Super-Targeting. Then the structure of the network is initialized through Pinch Design Method. Lastly, the optimal heat duties of the heat exchangers are specified by Differential Evolution method to get the minimum total annual cost.